Targeting phospholipase D pharmacologicallly prevents phagocytic function loss of retinal pigment epithelium cells exposed to high glucose levels - Tenconi, Paula Estefania (2022)
Objective: Inflammation and oxidative stress are a key factor in retinal and ocular diseases. We previously described the participation of classical phospholipase D isoforms (PLD1 and PLD2) in the inflammatory response of human retinal pigment epithelium (RPE) cells exposed to high glucose concentrations (HG). The aim of this work was to study the role of the PLD pathway in RPE phagocytic function. Materials and Methods: Two human RPE cell lines were used, ARPE-19 and ABC cells. ARPE-19 cells were exposed to HG (33 mM) or to normal glucose concentration (NG, 5.5 mM, control condition) for 24, 48 or 72 h and then non-specific phagocytosis was measured using pHrodo™ green bioparticles®. Also, photoreceptor outer segments (POS) phagocytosis was measured. To inhibit PLD1 and PLD2 cells were treated with 0.5 or 5 μM pharmacological PLD1 (VU0359595 or PLD1i) or PLD2 (VU0285655-1 or PLD2i) selective inhibitors. Also, PLD1 and PLD2 siRNA were used. Cell viability was measured by flow cytometry using propidium iodide (PI). Results: HG exposure for 48 and 72 h reduced phagocytic function of ARPE-19 cells. The loss of function induced by HG was prevented when cells were treated with 5 μM PLD1i or PLD2i. Furthermore, PLD1i and PLD2i did not affect RPE phagocytic function under physiological conditions and were able to prevent the increase in reactive oxygen species (ROS) induced by HG in RPE cells. In addition, RNAseq analyses showed for the first time PLD1 and PLD2 expression in hRPE49 and ABC cells, a novel human RPE cell line. Under physiological conditions, PLD1i and PLD2i did not affect ABC cells viability and partial silencing of both PLDs did not affect ABC cells POS phagocytosis. Conclusion: Our findings demonstrate that PLD1i and PLD2i prevent the loss of phagocytic function of RPE cells exposed to HG, without affecting RPE function or viability under non-inflammatory conditions, pointing to their potential use as therapeutic agents for retinal inflammatory diseases.